Letter : Ray Cox Memorial - Witt, L.
042-0128-001 THE JOINT COUNCIL of the SOUTHAMPTON TRADES COUNCIL, LABOUR PARTY and CO-OPERATIVE SOCIETY PROSPECT HOUSE, 160 ABOVE BAR, SOUTHAMPTON Hon. Secretary : Mr. L. WITT Telephone : 5191 Southampton Trades Council Hon. Secretary : Mr. R. Chick 107 Earls Road Southampton Labour Party Secretary and Agent : Mr. A. Rose 54 Henstead Road Telephone : 2427 Southampton Co-operative Society, Ltd. (Development Committee) Secretary : Mr. L. Witt, Prospect House 160 Above Bar Telephone : 5191 31st July, 1937. Mr. W. Citrine, Secretary, National Council of Labour, Transport House, Smith Square, London, S.W. 1. YOUR REF:- WMC/EAB/823. Dear Sir, RAY COX MEMORIAL. I beg to refer to your letter of 8th June, regarding the above. You will remember that in a previous letter you said you would arrange for a photograph of the Anaesthetic Apparatus to be taken and sent on to us. I shall be glad to know whether the Secretary of the I.F.T.U. has yet been able to get this done. We should be interested to receive a copy. Yours truly, L. Witt Hon.Sec. 292/946/42/128